Hydrogen and oxygen stable isotope dynamics of hyper-saline and salt-saturated aqueous solutions. (1st October 2018) - Oerter, Erik J.; Singleton, Michael; Davisson, M. Lee
Highlights: We studied hydrogen and oxygen stable isotope salt effects in water-salt mixtures from dilute to above salt-saturated. Isotope effects for BaCl2, K2 SO4, and NaBr are quantified and are a new addition to the literature. Hydrogen and oxygen isotope effects in vapor do not behave as systematically above salt saturation as at less than saturated. We make recommendations on the use of salts that exert hydrogen and oxygen isotope effects with the least magnitude. Abstract: An attractive tracer of water-surface interactions in humidity exposure experiments are the stable hydrogen and oxygen isotopes in water vapor, though the conventional method of using salt saturated aqueous solutions to control humidity is likely to exert strong effects on the H and O stable isotope composition of the vapor. The magnitude of these effects are virtually unknown for hyper-saline solutions near salt saturation and beyond. Here we explore the hydrogen and oxygen stable isotope effects of salt-water mixtures from dilute to the salt saturation point and beyond for BaCl2, CaCl2, KCl, K2 SO4, MgCl2, NaBr, NaCl, and NaI salts, of which the O isotope results on BaCl2, K2 SO4, and NaBr are the first to be reported, and the first for H with BaCl2 . We find that vapor humidity levels, and hydrogen and oxygen isotope effects in the vapor generated from dilute solutions to salt-saturated mixtures increase in magnitude by predictable linear trends. In the case of hydrogen isotope salt effects, the cation identity matters, as the effect becomes stronger with decreasing size and increasing charge (increasing ionic potential) in the sequence of: K < Na < Ba < Ca < Mg. For oxygen, the cation effect becomes stronger with increasing ionic potential, in the order of Na < Ba < K < Ca < Mg (irrespective of sign). Hydrogen and oxygen isotope effects in vapor from salt concentrations greater than the salt saturation point do not behave as systematically, with some of the salts displaying no increase in isotope effects beyond saturation, while others show an increase in isotope effects beyond salt saturation, especially in the case of hydrogen. We make specific recommendations on the salts that exert hydrogen and oxygen isotope effects with the least magnitude and most predictability for humidity levels from 26% to 92%. The use of salt solutions to create vapor at less than 100% and with specific δ 2 H and δ 18 O values that differ from that defined by the global meteoric water relationship also seems possible. Hyper-saline surface waters can exist at and above saturation, and thus these isotope effects may be present in them, as well as in minerals that form from these waters.